Physiological and performance adaptations to interval training in endurance-trained cyclists: An exploratory systematic review and meta-analysis - Norte, B.; Steele, J.; Wright, J. (International Journal of Strength and Conditioning, 2025)
Background: In endurance cycling, both high-intensity interval training (HIIT) and sprint interval training (SIT) have become popular training modalities due to their ability to elicit improvements in performance. Studies have attempted to ascertain which form of interval training might be more beneficial for maximising cycling performance as well as a range of physiological parameters, but an amalgamation of results which explores the influence of different interval training programming variables in trained cyclists has not yet been conducted.